An aural perception and aural comprehension achievement test in English for Grade II - Fortaleza, Angela Mendoza 1946- ([Quezon City s.n.], 1974)
This paper focuses on the construction and validation of an achievement test that may be used to determine aural perception and aural comprehension of English critical sounds, vocabulary and structural items generally considered difficult for Grade II Tagalog learners of English in District VI of Manila.
Thesis (M.Ed.)--University of the Philippines.
Keywords: English language -- Study and teaching; Comprehension -- Testing; Perception -- Testing